Structure-based drug discovery against a novel antimalarial drug target, S-adenosylmethionine decarboxylase/ornithine decarboxylase - Birkholtz, Lyn-Marie (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.